Metformin Ameliorates Podocyte Damage by Restoring Renal Tissue Podocalyxin Expression in Type 2 Diabetic Rats - Limin Zhai; Junfei Gu; Di Yang; Wei Wang; Shandong Ye (Journal of Diabetes Research)
Podocalyxin (PCX) is a signature molecule of the glomerular podocyte and of maintaining integrity of filtration function of glomerulus. The aim of this study was to observe the effect of different doses of metformin on renal tissue PCX expression in type 2 diabetic rats and clarify its protection on glomerular podocytes. Type 2 diabetic Sprague-Dawley (SD) rats in which diabetes was induced by high-fat diet/streptozotocin (HFD-STZ) were treated with different doses of metformin (150, 300, and 500 mg/kg per day, resp.) for 8 weeks. Various biochemical parameters, kidney histopathology, and renal tissue PCX expression levels were examined. In type 2 diabetic rats, severe hyperglycemia and hyperlipidemia were developed. Urinary albumin and PCX were markedly increased. Diabetes induced significant alterations in renal glomerular structure. In addition, protein and mRNA expression of renal tissue PCX were highly decreased. However, treatment of rats with different doses of metformin restored all these changes to a varying degree. These results suggested that metformin can ameliorate glomerular podocyte damage in type 2 diabetic rats, which may be partly associated with its role in restoring PCX expression and inhibiting urinary excretion of PCX with dose dependence.